Chronic Toxicity Study of Ethanol Extract from Voacanga foetida (Blume) Rolfe Leaves on Liver Biochemical and Histopathological Parameters in Male White Rats (Rattus norvegicus) - adriani susanty; Rilialita Lifiani; Aminah Kurniasih (Fakultas Farmasi Universitas Andalas, 2025)
This study aimed to evaluate the chronic toxicity of the ethanol extract of Voacanga foetida (Blume) Rolfe leaves onliver biochemical and histopathological parameters in male white rats (Rattus norvegicus). The animals were orally administeredthe extract daily for six months and divided into four groups: a control group and three treatment groups receiving doses of70, 140, and 210 mg/kg body weight (BW), respectively. Biochemical analyses included serum levels of albumin, total bilirubin, SGOT, SGPT, and triglycerides. Liver histopathological changes were observed both macroscopically and microscopically. The results showed that ethanol extract administration at all tested doses did not cause significant changes (p>0.05) in albumin, total bilirubin, SGOT, or triglyceride levels compared to the control. However, SGPT levels were significantly elevated (p<0.05) in the 140 and 210 mg/kg BW groups. Macroscopic examination revealed no alterations in liver color or texture across all groups. Microscopic observations indicated no structural damage to the central vein in the liver (p>0.05). In conclusion, subchronic oral administration of ethanol extract from V. foetida leaves up to 210 mg/kg BW for six months did not produce significant toxic effects on liver function or morphology in male rats